Réponses

  • Omnes
  • Modérateur confirmé
2014-03-23T21:50:41+01:00
Salut,

A = (5x - 3)² - (2x-1)(5x-3)
A = (5x-3)(5x-3)  - (2x -1)(5x - 3)
A = (5x-3)[5x - 3 - (2x-1)]
A = (5x - 3)(5x - 3 - 2x + 1)
A = (5x-3)(3x - 2)

B = 4x² + 8x + 4
B = (2x)² + 2 * 2x * 2 + 2²
B = (2x + 2)²

C = (x + 7)² - (2x - 5)² -> Reconnaissance de a² - b² = (a+b)(a-b)
C = [(x+7) + (2x-5)][(x+7) - (2x-5)]
C = (x + 7 + 2x - 5)(x+7 -2x +5]
C = (3x + 2)(12 -x)

Bonne soirée !
2014-03-23T22:12:29+01:00
A = (5x-3)²-(2x-1)(5x-3)  on met 5x-3 en facteur
A=(5x-3)[5x-3-(2x-1)]
A=(5x-3)(5x-3-2x+1)
A=(5x-3)(3x-2)

B=4x²+8x+4
B=(2x)²+8x+2²   identité remarquable (a+b)²=a²+2ab+b²
B=(2x+2)²

C=(x+7)²-(2x-5)²   identité remarquable a²-b²=(a+b)(a-b)
C=(x+7+2x-5)(x+7-2x+5)
C=(3x+2)(-x+12)